2015
DOI: 10.1111/disa.12168
|View full text |Cite
|
Sign up to set email alerts
|

Prioritisation of citizen‐centric information for disaster response

Abstract: In the aftermath of a disaster event, and in the absence of trained professionals, many responsibilities are assumed by uninjured citizens who are willing and able to help, such as care of the injured or search and rescue. These citizens are constrained by communications and logistics problems but are less equipped to deal with them as most often they are cut off from any coordinated assistance. The method proposed in this study would increase the survivability of those injured or trapped by a disaster event b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Studies have found that challenges around disaster information and knowledge management lie with risk interpretation and understanding, mentalities across scales, power structure, personal attitudes, values, and other constraints across individual, community, and agency levels [9] [40] [63]. Due to many of these barriers, a key component of disaster information-local knowledge and practices -has not yet been adequately incorporated into the official channels of disaster management [16] [41] [42]. While the importance of local knowledge has been widely recognized and advocated in relation to disaster, particularly for the most vulnerable populations, the practical application has so far been limited [18] [41].…”
Section: Shelter As An Information and Coordination Challengementioning
confidence: 99%
“…Studies have found that challenges around disaster information and knowledge management lie with risk interpretation and understanding, mentalities across scales, power structure, personal attitudes, values, and other constraints across individual, community, and agency levels [9] [40] [63]. Due to many of these barriers, a key component of disaster information-local knowledge and practices -has not yet been adequately incorporated into the official channels of disaster management [16] [41] [42]. While the importance of local knowledge has been widely recognized and advocated in relation to disaster, particularly for the most vulnerable populations, the practical application has so far been limited [18] [41].…”
Section: Shelter As An Information and Coordination Challengementioning
confidence: 99%
“…Each of these papers was examined and, notwithstanding the search string, 38 were found to be not directly relevant as they discussed, for example, the broader challenge of post-disaster information management (Milliken and Linton, 2016), the use of RPAS as part of an occupational hygiene programme (Eninger and Johnson, 2015), or contained dated material that was no longer relevant. This category also included literature reviews of the HL field (such as those of Kunz and Reiner, 2012; Leiras et al , 2014) and more general discussions of the HL challenges offered by Tatham and Pettit (2010) and Tatham and Christopher (2014), both of which mention the potential use of RPAS without offering any specific analysis.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The results of this review (Table II) were used to update an earlier review by Tatham et al (2017) which discussed the general operation of RPAS in support of the logistic response to disasters. Each of these papers was examined and, notwithstanding the search string, 41 were found to be not directly relevant as they discussed, for example, the use of RPAS in agriculture (Zhang and Kovacs, 2012) or the broader challenge of post-disaster information management (Milliken and Linton, 2016). This category also included literature reviews of the HL field (such as those of Kunz and Reiner, 2012;Leiras et al, 2014) and more general discussions of the HL challenges offered by Tatham and Pettit (2010) and by Tatham and Christopher (2014), both of which mentioned the potential use of RPAS without offering any specific analysis.…”
Section: Use Of Rpas In Disaster Responsementioning
confidence: 99%